The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0100-72032007000600001
|View full text |Cite
|
Sign up to set email alerts
|

Vacinas profiláticas para o HPV

Abstract: EditorialInfecções estão intimamente ligadas às neoplasias. Cerca de um quinto dos cânceres são conseqüência da presença de algum agente infeccioso e, com larga vantagem, figura o papilomavírus humano (HPV) como o organismo infectante mais apto a provocar neoplasias. Nem todos os tipos de HPV, entretanto, são capazes de originar tumores, sendo o 16 e o 18 os responsáveis por 60% dos casos de câncer de colo do útero em todo o mundo. Os HPV tipos 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 68, 73 e 82 também são co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
6
Order By: Relevance
“…Several studies demonstrated the efficacy of the HPV vaccine in the prophylaxis and reduction of the morbidity and mortality that is associated with anogenital HPV infection (19,20) . Conversely, the authors of an editorial that was published in the Brazilian Journal of Gynecology and Obstetrics (Revista Brasileira de Gineco Obstetrícia) in 2007 stated that if a program of massive HPV vaccination was developed, the epidemiological effects may not be evident for several years, and there would be no significant effect on cervical cancer screening (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the efficacy of the HPV vaccine in the prophylaxis and reduction of the morbidity and mortality that is associated with anogenital HPV infection (19,20) . Conversely, the authors of an editorial that was published in the Brazilian Journal of Gynecology and Obstetrics (Revista Brasileira de Gineco Obstetrícia) in 2007 stated that if a program of massive HPV vaccination was developed, the epidemiological effects may not be evident for several years, and there would be no significant effect on cervical cancer screening (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Estudo conduzido em Campinas buscando analisar o conhecimento de homens e mulheres acerca do HPV e das vacinas e a intenção de vacinarem seus filhos adolescentes ressaltou a necessidade de intervenções educativas na população para prover informação adequada sobre o HPV e sobre medidas de prevenção (DUARTE-OSIS et al, 2014). Segundo Derchain et al (2007) uma eficácia de 95% da vacina associada a uma cobertura de 80%, tendo a vacina os antígenos do HPV 16, 18 e 45 teoricamente levaria a uma redução de 59% na incidência do carcinoma cervical.…”
Section: Figura 2 Distribuição Da Cobertura De Vacina Contra Hpvunclassified
“…It can lead to a variety of benign, premalignant and malignant lesions in the mucosa and cutaneous tissues 1 . Genital HPV infection is one of the most frequent sexually transmitted diseases 2,3 . In a high prevalence context, infectivity and diagnosis are made by examining the clinical, subclinical and asymptomatic lesions; the dissemination of HPV is universal among the sexually active population, where men are an important means for the proliferation of the virus [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Genital HPV infection is one of the most frequent sexually transmitted diseases 2,3 . In a high prevalence context, infectivity and diagnosis are made by examining the clinical, subclinical and asymptomatic lesions; the dissemination of HPV is universal among the sexually active population, where men are an important means for the proliferation of the virus [1][2][3][4] . It is estimated that 15 to 40% of the world's population is contaminated with HPV 5,6 ; furthermore, more than 500,000 new cases occur worldwide every year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation